Estrategias metodológicas para el aprendizaje del Movimiento en una Dimensión en la Unidad Educativa Fernando Daquilema - Moreta Morocho, Carlos Danilo (2024)
This project studies methodological strategies employed in learning onedimensional motion at the Fernando Daquilema High School. This type of motion presents significant challenges for students due to its abstract nature and various concepts such as displacement, velocity, and acceleration, making it difficult for many to learn these contents. Thus, this research aims to develop a guide of methodological strategies for learning One-Dimensional Motion at the Fernando Daquilema High School. The research has a quantitative approach of transversal type with a non-experimental design and a descriptive-propositional level. For the sample selection, a non-probabilistic intentional sampling was applied, with a total of 54 individuals. The data collection technique used was a survey with a questionnaire as the instrument. The results show that the most used strategies for learning one-dimensional motion are interactive lecture classes and problem-solving; however, ICT was rarely used for learning the subject mentioned above. Finally, an activity guide based on methodological strategies was developed.